Financial market and capital flow dynamics during the COVID-19 pandemic - John Beirne; Nuobu Renzhi; Eric Sugandi; Ulrich Volz (Asian Development Bank Institute (ADBI), 2020)
This paper empirically examines the reaction of global financial markets across 38 economies to the COVID-19 outbreak, with a special focus on the dynamics of capital flow across 14 emerging market economies. Using daily data over the period 4 January 2010 to 30 April 2020 and controlling for a host of domestic and global macroeconomic and financial factors, we use a fixed effects panel approach and a structural VAR framework to show that emerging markets have been more heavily affected than advanced economies. In particular, emerging economies in Asia and Europe have experienced the sharpest impact on stocks, bonds, and exchange rates due to COVID-19, as well as abrupt and substantial capital outflows. Our results indicate that fiscal stimulus packages introduced in response to COVID-19, as well as quantitative easing by central banks, have helped to restore overall investor confidence through reducing bond yields and boosting stock prices. Our findings also highlight the role that global factors and developments in the world's leading financial centers have on financial conditions in EMEs. Importantly, the impact of COVID-19 related quantitative easing measures by central banks in advanced countries, which helped to lower sovereign bond yields and prop up stock markets at home, extended to EMEs, notably in relation to stabilizing capital flow dynamics. Going forward, while the ultimate resolution of COVID-19 may be expected to lead to a market correction as uncertainty declines, our impulse response analysis suggests that there may be some permanent effects on financial markets and capital flows as a result of COVID-19, particularly in EMEs.
Keywords: F32; F41; F62; 330; COVID-19; financial markets; capital flows